Analisis kimia dan uji oragnoleptik pada minuman sinbiotik dengan penambahan ektrak pati sagu - Anjar Briliannita; Zaenab Ismail (Politeknik Kesehatan Kemenkes Aceh, 2021)
Background: Sago is local food, contains lactic acid bacteria that can ferment high carbohydrates and oligosaccharides purified from sago extract. It has the potential as a prebiotic because it can support the growth of lactic acid bacteria, reduce the growth of E.coli and Salmonella bacteria (in vitro).Objectives: To determine the effect of synbiotic drink added with sago starch extract (Metroxylon sago r) on organoleptic and nutritional tests and determine the degree of acidity of the drink.Methods: Experimental study with a completely randomized design (CRD). Organoleptic tests at the Nutrition Laboratory of the Nutrition Department of the Health Polytechnic of Sorong and chemical tests at the Chemix Pratama Laboratory in Yogyakarta in April-June 2020. Descriptive univariate analysis, including frequency and percentage distribution. Bivariate test with ANOVA test and Duncan's follow-up test.Results: The results showed that the synbiotic drink (yogurt) added with sago starch extract and using starter Streptococcus thermophilus, and Lactobacillus bulgaricus had a significant effect on the organoleptic test and the carbohydrate content of the product ( p < 0.05). The most preferred synbiotic drink (yogurt) from the three drink variations (Y011, Y021, and Y033) drinks Y021. The analysis of starch content in local varieties of West Papua sago flour was very high, namely 83.30%, and the chemical test results of acidity (pH) in the selected synbiotic drink (yogurt) Y021 was 4.36.Conclusion: The synbiotic drink added with sago starch extract had a significant effect on the organoleptic test compared with commercial yogurt drink and the carbohydrate content of the drink. Of the 3 variants of sago starch extract in synbiotic drinks, selected was Y021, and the best degree of acidity in synbiotic drinks (Y021), pH = 4.36 was sufficient to meet the standard of acidity of yogurt drinks in general.